Human Erythrocyte Superoxide Dismutase Encapsulated in Positively Charged Liposomes: Superoxide dismutase encapsulated in liposomes - Ghaffari, Mohammad Ali; Dabbagh, Mohammad Ali; Gharib, Amir (Iranian Journal of Pharmaceutical Sciences, 2005)
Superoxide dismutase (SOD) is an important antioxidant that protects many types of cells from the free radical damage. One of the possible ways for the use of SOD is its incorporation in liposomes. The aim of this study was to investigate the effect of cationic phospholipids on the entrapment of human erythrocyte superoxide dismutase (Cu/Zn SOD) in liposomes. Also, in the present study, we examined the effect of this formulation on the permeability of these liposomes for SOD at two different temperatures (4 °C and 37 °C). Cu/Zn SOD was purified from human erythrocytes. Several methods, including, precipitation by acetone, chloroform, centrifugation and also ion exchange chromatography on DEAE-32 were applied. In this study, encapsulated SOD in liposomes was prepared using the film hydration method. The results obtained from the prepared human erythrocyte SOD showed that at the end of the last stage, the purification was 21 times the result of the first stage, with a specific activity of 3000 U/mg. The enzyme activity and the retained enzymatic activity in liposome solution were 74±0.2 U/mg and 45%, respectively. Incubation of SOD-liposomes at 4 °C and 37 °C for 8 hours, caused the enzyme activity to decrease to 66±0.2 U/mg and 31±0.2 U/mg, respectively. The present study showed that preparation of the liposomes with cationic phospholipids was an important role in the increase of the entrapped enzyme.